Islamic Moderation Education in the Concepts of Wahdat al-Wujud and Wahdat asy-Syuhud - Ilman Nafi'a; Septi Gumiandari (Jurnal Penelitian, 2022)
The teachings of Sufism play an essential role in balancing human life. Sufism can practically be the driving force to provide peace, coolness, and friendliness to create religious and social harmony. This study aims to explain the values of religious moderation education reflected in the concepts of wahdat al-Wujud and wahdat asy-Syuhud. This study used qualitative methodology with a literature approach. The primary sources are taken from two books: wahdat al-Wujud 'Inda Ibn Arabi by Abdul Karim Ibn Abdul Jalil and Ibn al-Faridh wa al-Hubb al-Ilahi by Muhammad Mustafa Hilmi, while the secondary ones are references taken from journals, books, and other writings that explain Islamic moderation, philosophical Sufism, and educational values. The results showed that the concept of monotheism carried by Ibn Arabi’s wahdat al-Wujud and Ibn al-Faridh’s wahdat asy-Syuhud, in the context of the issues of religious moderation, does not only discuss a single divinity, but it also offers five ideas: (1) equality of relationship between people, (2) human rights, (3) tolerance in religious plurality, (4) harmony in religious life, and (5) values of Islamic moderation Education.